AN ANALYSIS OF STUDENTS’ ERROR IN TRANSLATING INDONESIAN SENTENCES INTO ENGLISH - Wirentake, Wirentake (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2022)
This research was an error analysis of the first semester students of Sumbawa University of Technology. The aims of the research were to find out what types of error that the students committed and what error that they committed the most. The research was a descriptive study, where the population of the research was all first semester students, while the sample was Electrical Engineering Class which consists of 34 students. The technique data collection was by giving the students translation tests. The data was analyzed by identifying, classifying, and describing the errors. Based on the result of analysis, it was found that (1) there were four types of error that students committed, they were omission, addition, misordering and misformation error: (2) type of error that students committed the most was omission, and the least error was miordering.